Associations between Features of External Ventricular Drain Management, Disposition, and Shunt Dependence - Engel, Corey; Faulkner, Amanda L.; Van Wyck, David W.; Zomorodi, Ali R.; King, Nicolas K. Kam; Williamson Taylor, Rachel A.; Hailey, Claire E.; Umeano, Odera A.; McDonagh, David L.; Li, Yi-Ju; James, Michael L.; for the Duke Critical Care Outcomes Research Endeavors (C-CORE) group (Journal of Neuroanaesthesiology and Critical Care, 2020)
Background In the United States, nearly 25,000 patients annually undergo percutaneous ventriculostomy for the management of increased intracranial pressure with little consensus on extraventricular drain management. To characterize relationships between external ventricular drain management, permanent ventriculoperitoneal shunt placement, and hospital disposition, we hypothesized that patients requiring extended drainage would have greater association with ventriculoperitoneal shunt placement and unfavorable disposition.Methods Adult patients admitted to the Duke University Hospital Neuroscience Intensive Care Unit between 2008 and 2010 with extraventricular drains were analyzed. A total of 115 patient encounters were assessed to determine relative impact of age, sex, days of extraventricular placement, weaning attempts, cerebrospinal fluid drainage volumes, Glasgow Coma Scale, and physician’s experience on disposition at discharge and ventriculoperitoneal shunt placement. Univariate logistic regression was first used to test the effect of each variable on the outcome, followed by backward selection to determine a final multivariable logistic regression. Variables in the final model meeting p < 0.05 were declared as significant factors for the outcome.Results Increased extraventricular drain duration (odds ratio [OR] = 1.17, confidence interval [CI] = 1.05–1.30, p = 0.0049) was associated with ventriculoperitoneal shunt placement, while older age (OR = 1.05, CI = 1.02–1.08, p = 0.0027) and less physician extraventricular drain management experience (OR = 4.04, CI = 1.67–9.79, p = 0.0020) were associated with unfavorable disposition.Conclusion In a small cohort, exploratory analyses demonstrate potentially modifiable factors are associated with important clinical outcomes. These findings warrant further study to refine how such factors affect patient outcomes.
Keywords: ventriculostomy; ventriculoperitoneal shunt; adult; weaning; drainage; intracranial pressure